2016
DOI: 10.1259/dmfr.20150419
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of computer-aided detection system in diagnosing unilateral maxillary sinusitis on panoramic radiographs

Abstract: The CAD system supported the inexperienced dentists in diagnosing maxillary sinusitis on the panoramic radiographs. If the accuracy of the CAD system can be increased, the benefits of CAD support will be further enhanced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 21 publications
(31 reference statements)
0
20
1
Order By: Relevance
“…The 50 studies reporting applications of AI models to analyze 2D/3D images in the dental and maxillofacial region covered a period from November 1992 to January 2019 ( Figure 2). In these studies, six [27][28][29][30][31][32] used periapical radiographs,14 [33][34][35][36][37][38][39][40][41][42][43][44][45][46] used panoramic radiographs, one 47 used both intraoral and panoramic radiographs, ten [48][49][50][51][52][53][54][55][56][57] The Use and Performance of AI Applications in DMFR Hung et al used cephalometric radiographs, 14 [58][59][60][61][62][63][64][65][66][67][68][69][70][71] used CBCT images, one 72 used intraoral photographs, one…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 50 studies reporting applications of AI models to analyze 2D/3D images in the dental and maxillofacial region covered a period from November 1992 to January 2019 ( Figure 2). In these studies, six [27][28][29][30][31][32] used periapical radiographs,14 [33][34][35][36][37][38][39][40][41][42][43][44][45][46] used panoramic radiographs, one 47 used both intraoral and panoramic radiographs, ten [48][49][50][51][52][53][54][55][56][57] The Use and Performance of AI Applications in DMFR Hung et al used cephalometric radiographs, 14 [58][59][60][61][62][63][64][65][66][67][68][69][70][71] used CBCT images, one 72 used intraoral photographs, one…”
Section: Study Characteristicsmentioning
confidence: 99%
“…With regard to the applications of these AI models, 19 [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65]75 reported on localization/measurement of cephalometric landmarks, nine [35][36][37][38][39][40][41][42][43] on diagnosis of osteoporosis, six 33,34,[67][68][69]76 on classification/segmentation of maxillofacial cysts and/or tumors, three [27][28][29] on identification of alveolar bone resorption, three 30,31,66 on classification of periapical lesions, two 47,74 on the diagnosis of multiple dental diseases, and two 46,72 on classification of tooth types. Furthermore, single studies were found for the identification of root canals, 71 diagnosis of the maxillary sinusitis, 45 identification of inflamed gingiva, 73 identification of dental plaque, 70 detection of den...…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, these systems can be used in medicine and, particularly, in dentistry [9,10,11,12]. The expert system can be used for many medical and diagnostic purposes: to solve problems of diagnostics, to establish the diagnosis, to appoint medical measures, to predict the course of the disease and to prevent threatening complications [13]. Our sphere of interest is the treatment of patients with various diseases of the maxillofacial area, so it remains relevant to improve the diagnosis and treatment of patients with odontogenic maxillary sinusitis (OMS), as one of the most common pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…Although panoramic radiography has been recognized as an essential tool in dental practice for more than half a century, panoramic image appearances are occasionally difficult to interpret, especially for structures adjacent to the maxillary sinus. 1 This can be mainly attributed to the complexity of anatomical variations in the maxillary sinus area and their relationships with X-ray beam projection angles in panoramic radiography. Meanwhile, CT and CBCT for dental use enable us to clearly visualize the anatomical structures adjacent to the maxillary sinus, and many studies have been performed on various diseases 2,3 and maxillary sinus morphologies, including volume 4,5 and sinus septa.…”
Section: Introductionmentioning
confidence: 99%